A palace for those who have eyes to see: Preliminary remarks on the symbolic geography of Reting (Rwa-sgreng) - Roesler, Ulrike (Acta Orientalia Vilnensia, 2007)
University of Freiburg An important feature in Tibetan ‘constructions of place’ is the cult of mountain gods, in which a central mountain is venerated as the lord of the surrounding territory and the people living in his realm. In the present study, it is not a mountain god, but a newly founded Buddhist monastery that assumes the central position and thereby the notions of centrality and royal power: Rwa-sgreng, the first monastic seat of the bKa’-gdams-pa school. ’Brom-ston, the founder of the school, is described as the heir of a highly symbolical legacy, since he comes to be regarded as an incarnation of Tibet’s first Buddhist king, Srong-btsan sgam-po, and as a manifestation of Avalokiteśvara, the Bodhisattva of compassion. Through this literary construction of place in space and in time, the significance of the bKa’-gdams-pa school itself is re-assessed and amplified. The sources discussed here exhibit slightly different attitudes: The earliest work, a biography of ’Brom-ston, describes the landscape as a natural maṇḍala with auspicious features. The slightly later ‘Book of the bKa’-gdams [tradition]’ shifts to a ‘pure vision’ of the place and identifies ’Brom-ston with King Srong-btsan sgam-po and Avalokiteśvara. The last work is a pilgrimage guide that gives practical advice for visitors. An unexpected feature in this work is the notion of evil influences ascribed to certain places, slightly undermining the success of the appropriation of the site by the Buddhist tradition.